Simulated Pain and Cervical Motion in Patients with Chronic Disorders of the Cervical Spine - Zeevi Dvir; Noga Gal-Eshel; Boaz Shamir; Evgeny Pevzner; Chava Peretz; Nachshon Knoller (Pain Research and Management)
The primary objective of the present study was to determine how simulated severe cervical pain affects cervical motion in patients suffering from two distinct chronic cervical disorders: whiplash (n=25) and degenerative changes (n=25). The second objective was to derive an index that would allow the differentiation of maximal from submaximal performances of cervical range of motion. Patients first performed maximal movement of the head (maximal effort) in each of the six primary directions and then repeated the test as if they were suffering from a much more intense level of pain (submaximal effort). All measurements were repeated within four to seven days. In both groups, there was significant compression of cervical motion during the submaximal effort. This compression was also highly stable on a test-retest basis. In both groups, a significantly higher average coefficient of variation was associated with the imagined pain and it was significantly different between the two clinical groups. In the whiplash group, a logistic regression model allowed the derivation of coefficient of variation-based cutoff scores that might, at selected levels of probability and an individual level, identify chronic whiplash patients who intentionally magnify their motion restriction using pain as a cue. However, the relatively small and very stable compression of cervical motion under pain simulation supports the view that the likelihood that chronic whiplash patients are magnifying their restriction of cervical range of motion using pain as a cue is very low.